Healing Through Reckoning: Black Feminist Pedagogies of Vulnerability, Healing, and Love - Keon M. McGuire; Valencia Clement (International Journal of Qualitative Methods)
Black feminist, womanist, and queer activist-intellectuals have deepened understandings of how intersecting systems of power—such as heteropatriarchy, misogynoir, and respectability—uniquely constrain Black lives through constructions of gender, sexuality, class, ability, and religion. Building on this work, our study investigates how Black cisgender college men navigate being both socially constructed as problems and experiencing societal problems within the pervasive context of anti-Blackness, heteropatriarchy, misogynoir, and transphobia. While college offers opportunities for gender exploration and transformation, it often reinforces binary and racialized conceptions of gender that limit such possibilities. Guided by Black feminist pedagogies, this study examines how these men, through engagement with Black feminist texts and perspectives, encounter pathways of repair and transformation that challenge restrictive norms of masculinity. By exploring masculinities as plural and not rooted in biological determinism, this research offers empirical insights into how Black feminist frameworks create opportunities for healing, wholeness, and reimagined gender embodiments for Black men in higher education.